2022
DOI: 10.1039/d2fo02625b
|View full text |Cite
|
Sign up to set email alerts
|

Effects of curcumin, a bioactive component of turmeric, on type 2 diabetes mellitus and its complications: an updated review

Abstract: Type 2 Diabetes Mellitus (T2DM) is a substantial issue in public health. Recently, there has been considerable interest in the effectiveness of using herbal supplements in T2DM. Among the herbal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 81 publications
1
15
0
Order By: Relevance
“…It modulates inflammatory pathways by inhibiting transcription factors activation such as Nuclear Factor-κB which is a potential method for the diagnosing and managing the Inflammatory CVD and reducing the interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) expression, which are pro-inflammatory cytokines [ 64 66 ]. By doing so, curcumin helps mitigate chronic inflammation, which is a common feature of various chronic diseases, including DM2 [ 64 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It modulates inflammatory pathways by inhibiting transcription factors activation such as Nuclear Factor-κB which is a potential method for the diagnosing and managing the Inflammatory CVD and reducing the interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) expression, which are pro-inflammatory cytokines [ 64 66 ]. By doing so, curcumin helps mitigate chronic inflammation, which is a common feature of various chronic diseases, including DM2 [ 64 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin possesses strong antioxidant properties [ 67 ]. It scavenges free radicals and ROS, thereby reducing oxidative stress [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research study reported that curcumin had affected the enzyme PTP1B by increasing the sensitivity of hepatic leptin and insulin of rat liver [14,15]. Curcumin also inhibited PTP1B enzyme action that leads to improve hepatic leptin and insulin signaling in rats fed with fructose [16][17][18][19][20]. In addition, curcumin remarkably reduced the podocyte injury and proteinuria induced by fructose, the expression of PTP1B, and cut down the activity of insulin receptor and insulin receptor substrate 1 of fructose-fed rats [21].…”
Section: Introductionmentioning
confidence: 98%
“…CUR is a natural yellow pigment that has attracted much attention in recent years owing to its wide spectrum of biological properties, including antioxidant, anti-inflammatory, anti-tumour, and anti-microbial activities [ 20 , 21 ]. CUR improved cardiovascular structure and function, especially with the normalisation of systolic blood pressure (SBP) and collagen deposition in rats with diet-induced metabolic syndrome [ 22 ].…”
Section: Introductionmentioning
confidence: 99%